Chronic blepharitis like picture in patients with Discoid lupus erythematosis – Case series - Jisha, K.; Rajesh, P.S.; Kurien, George; Sathish, Gargi; Vijayamma, N. (Nepalese Journal of Ophthalmology, 2018)
Background: Blepharitis is a very common condition encountered in ophthalmology outpatient care department. Dermatological diseases like seborrheic keratopathy and rosacea have been frequently discussed as being associated with blepharitis. However Discoid lupus erythematosis [DLE], an autoimmune condition has only rarely been reported to involve the eyelids mimicking blepharitis. DLE affecting the eyelids can produce significant morbidity with lid deformities, trichiasis and symblepharon if left untreated.Objective: To report three consecutive cases of DLE with eyelid lesions mimicking blepharitis. They presented to the department of ophthalmology at our institute from April 2014 to March 2016. The first case presented with involvement of lower eyelid in one eye. She was having multiple skin lesions which on biopsy confirmed the diagnosis of DLE. The second case was a diagnosed case of DLE who received treatment 4 years back and came with relapse of the disease affecting the eyelid. The third case was a recently biopsy confirmed case of DLE with multiple skin lesions along with bilateral eyelid involvement. Two of them had madarosis and one case had destruction of the outer lid margin at presentation. All three cases responded well to treatment with Hydrxychloroquin.Conclusion: The discoid lesions of DLE affecting the eyelids can mimic the appearance of chronic blepharitis. Ophthalmologists should be aware that DLE is a possibility while dealing with an atypical case of chronic blepharitis. Early diagnosis and treatment can prevent deformities of eyelid.